Modelling of SWOT Analysis Using Fuzzy Integrals - Haile, Meaza; Křupka, Jiří (Future Academy, 2016)
To develop a strategy for an organization it is important to understand the organization and its surrounding environment. SWOT(Strength, Weakness, Opportunity and Threat) analysis is a famous tool to perform this task precisely by showing the strength, weakness of the organization and the external factors, opportunities and threats that affect its success. SWOT analysis is commonly used by business; however non-profit organizations also use SWOT analysis for decision-making and strategy evaluation. The limitation of SWOT analysis is it does not give weight for the factors and there is no quantified result from the analysis. The methods introduced in this paper are Sugeno lambda measure and Choquet fuzzy integral. Sugeno lambda measure is used to aggregate the importance of characteristics and Choquet fuzzy integral is used for the overall analytical evaluation of strength, weakness, opportunity and threat of a specific organization. A case study has been conducted for a currency exchange office to explain the application of the proposed approach
Modelování SWOT analýzy pomocí fuzzy integrálů
Keywords: Choquet and Sugeno fuzzy integrals; Sugeno λ-measure; SWOT analysis; Choquet a Sugeno fuzzy integrály; Sugeno λ-míra; SWOT analýza